Trade Liberalization and Firm Performance: The Case of Thailand - Feliciano, Zadia M (Archīum Ateneo, 2020)
After the Asian Financial Crisis, Thailand's trade policy has been driven by the proliferation of free trade agreements (FTAs). We use firm-level data to estimate the effects of reductions in tariffs applied to Thai imports on Thai firms. Reductions in Association of Southeast Asian Nations (ASEAN) tariffs were associated with increasing firm employment and exports, lower ASEAN-China import tariffs were associated with increasing firm employment, while lower tariffs from the Japan-Thailand FTA were associated with reductions in firm employment and increasing likelihood of International Organization for Standardization (ISO) certifications. FTAs were associated with a decrease in firm R&D spending. (JEL F1, F2, F6)